The basic principles of water management (Journal of actual problems of jurisprudence, 2018)
In this article the basic principles of water management in conditions of market relations of the Republic of Kazakhstan. Multi-purpose nature of the use of water resources makes it necessary to establish priorities for water use. Priority is to meet the needs of the population in drinking water, the reservation for that purpose groundwater reserves. Provision of water supply reliability regulatory other sectors of the economy and restrictions on the use of water in dry years.Key words: principles, water resources, water management, rational use of water, water law, water relationship.